A Human – Never a Person, Always a Product : The Normalization of Atrocity in Agustina Bazterrica’s Tender Is the Flesh - Schuurman, Selina (My University, 2026)
This thesis examines how the atrocity of cannibalism is normalized in Agustina Bazterrica’s Tender Is the Flesh (2020), a novel that depicts a society in which the consumption of human flesh becomes socially accepted despite its status as a cultural taboo. I argue that manipulative language and institutionalized violence together construct the conditions in which atrocity can be normalized, and that social conformity, the class system and the loss of empathy perpetuate the normalized atrocity. I additionally draw on Margaret Atwood’s The Handmaid’s Tale (1985), as it offers thematically relevant points of comparison due to its dystopian themes of exploiting humans for one's own gain. To better understand an individual’s capability to create and partake in atrocities, I draw on Albert Bandura’s works on moral disengagement, in which he primarily argues that unethical acts are not necessarily done by evil individuals. Rather, different psychological processes and social conditions enable people to disengage morally, which then allows them to cross ethical boundaries. This thesis demonstrates that the normalization of cannibalism emerges from the connection of linguistic, institutional, and social processes that gradually reshape moral perception. The novel ultimately suggests that extreme violence does not require inherently cruel individuals, but conditions that enable moral disengagement, thereby highlighting the fragility of moral boundaries.
Keywords: cannibalism; atrocity; dehumanization; moral disengagement; Agustina Bazterrica